Sociodemographic Determinants of Households’ Food Waste in Garissa Sub County, Kenya - Julius M. Huho; Rose C. Kosonei; Peter, K. Musyimi (Budapest International Research and Critics University, 2020)
Food waste occurs when food is ready for consumption but not consumed. Food waste has considerable social, economic and environmental impacts. Even though it has become a global concern, no comprehensive studies on food waste in Kenya is available. This study sought to establish the sociodemographic determinants of households’ food waste in Garissa sub-county, in Garissa County, Kenya. A total of 165 consumers were involved in the study. Bakery products were the most wasted. The per capita food wasted was 6.1 kg/person/year or approximately 5.1 tonnes (equivalent to 39,352,110 Kcal) for Garissa County. At a per capita consumption of 2360 Kcal/ person/day, the food wasted was enough to feed 16,674 people for one day. Males were more wasteful than females. Food waste was higher in households: headed by people aged 25 – 34 years; with higher income; with urban residency and with large sizes. Annually, Kshs 9600 (US96) per household was lost from the wasted food translating to a loss of Kshs 1.4 billion (US 13.6 million) from the 141,353 households in Garissa County. With guidance and good policies, food waste can be managed since the majority of the consumers were concerned about food waste and had intentions to reduce it.